Inelastic neutron scattering study of crystalline electric field excitations in a cubic compound PrMgNi4. Issue 1 (1st March 2022) - Kusanose, Y.; Onimaru, T.; Yamane, Y.; Umeo, K.; Takabatake, T.; Guidi, T.; Le, D.; Adroja, D.T.
Abstract: We performed inelastic neutron scattering experiments on PrMgNi4 with the cubic MgSnCu4 -type structure. The magnetic excitations were observed at 1.1, 2.5, 5.9, 10.7, and 11.7 meV. Since the energy of the excitations is constant for | Q | < 5 Å −1, they are ascribed to the crystalline electric field (CEF) excitations of the Pr 3+ ions. We adopted CEF parameters of W = −3.3 K and x = 0.8 for the cubic T d point group to reproduce the strong excitations at 1.1, 10.7, and 11.7 meV. The calculated CEF level scheme reveals the Γ3 doublet ground state with the quadrupolar degrees of freedom and the excited states of Γ4 triplet (1.4 meV), Γ1 singlet (3.4 meV), and Γ5 triplet (13.5 meV). This scheme, however, does not explain the observed two excitations at 2.5 and 5.9 meV. These additional excitations may arise from splitting of the doublet by symmetry lowering due to excess Mg atoms occupying the Pr sites. This splitting is probably responsible for the absence of the long-range quadrupole order in PrMgNi4 .